A photonic crystal fiber splice with a standard single mode fiber - Murawski, Michał; Jaroszewicz, Leszek R.; Stasiewicz, Karol (Photonics Letters of Poland, 2009)
We report on the optimization of a fused splice between a photonic crystal fiber (PCF) with a standard single mode fiber (SMF) made by the filament fusion with continuous laser illumination. For the SMF 28 connection with a PCF having a similar mode field diameter splice losses are lower than 0.40 dB in comparison with the reported dependences in a spectral range of 1.51-1.63um. Based on the results obtained two aspects of splice are discussed: the mentioned above wavelength dependences as well as an observed nonreciprocal phenomenon according to light propagation through the splice. The discussed data have shown that such a SMF-PCF splice is suitable for the construction of a patch cord for measurement devices. Full Text: PDF References: B. Bourliaguet et al."Microstructured fiber splicing", Opt. Express 11, 3412 (2003).[CrossRef] P.J. Bennet et al."Toward practical holey fiber technology: fabrication, splicing, modeling, and characterization", Opt. Lett. 24, 1203 (1999).[CrossRef] J.T. Lizier, G.E. Town, "Splice losses in holey optical fibers", IEEE Photon. Techn. Lett. 13, 794 (2001).[CrossRef] R.K Sinha, K.V. Sailendra, "Estimation of splice loss in photonic crystal fibers ", SPIE 4655, 296 (2002).[CrossRef] A.D. Yablon, R.T. Bise, "Low-loss high-strength microstructured fiber fusion splices using GRIN fiber lenses", IEEE Photon. Techn. Lett. 17, 180120 (2005).[CrossRef] L. Jin W. Xiao, M.S. Demokan, "Fusion splicing small-core photonic crystal fibers and single-mode fibers by repeated arc discharges", Opt. Lett. 32, 115 (2007).[CrossRef] J.T. Kristensen et al. "Low-loss polarization-maintaining fusion splicing of single-mode fibers and hollow-core photonic crystal fibers, relevant for monolithic fiber laser pulse compression", Opt. Express 16, 9986 (2008).[CrossRef] L. Dong et al. "Highly nonlinear silica suspended core fibers", Opt. Express 16, 16423 (2008).[CrossRef] Corning SMF-28TM CPC6 Single-Mode Optical Fiber, Product Information, http://www.corningfiber.com Large Mode Area Photonic Crystal Fiber LMA-8, Product Information, http://www.crystal-fibre.com L.R. Jaroszewicz, M. Murawski, K. Stasiewicz, and P. Marć, Proc. SPIE 7503, 214 (2009) in press